Financial reporting standards: Global or international? - Frederick Lindahl; Hannu Schadewitz (Richards College of Business, University of West Georgia, 2022)
Purpose - This paper studies quantitative, monetary information about differences between IFRS and US GAAP in the three principal financial statements.
Design/methods/approach - Comparative data from the same company are compared. The explanations of differences are found in lengthy footnotes. The sample is from civil law countries with reputations for high integrity, reducing possible confounding effects of legal systems or earnings management. Sample countries are highly economically developed, reducing distortions that would result from different fair value conditions.
Findings - A few key standards account for most of the monetary differences between the accounting standards. In some cases large differences in one direction offset large differences in the other direction, reducing the insights from comparing only income.
Research limitations/implications - The window of data availability for single--company reporting under both standards was narrow. However, because of convergence activities, these differences are likely slowly to decline.
Originality/value - The only paper to examine the footnote disclosure in sufficient detail to accurately measure differences. The only paper to analyze the cash flow statement. It is valuable for financial analysts, and to academic researchers who study accounting quality and make international comparisons.